Blockade of p38 kinase impedes the mobilization of protumorigenic myeloid populations to impact breast cancer metastasis. Issue 8 (28th May 2020) - Zonneville, Justin; Colligan, Sean; Grant, Sydney; Miller, Alexandra; Wallace, Paul; Abrams, Scott I.; Bakin, Andrei V.
Abstract: Patients with metastatic breast cancer (MBC) have limited therapeutic options and novel treatments are critically needed. Prior research implicates tumor‐induced mobilization of myeloid cell populations in metastatic progression, as well as being an unfavorable outcome in MBC; however, the underlying mechanisms for these relationships remain unknown. Here, we provide evidence for a novel mechanism by which p38 promotes metastasis. Using triple‐negative breast cancer models, we showed that a selective inhibitor of p38 (p38i) significantly reduced tumor growth, angiogenesis, and lung metastasis. Importantly, p38i decreased the accumulation of myeloid populations, namely, myeloid‐derived suppressor cells (MDSCs) and CD163 + tumor‐associated macrophages (TAMs). p38 controlled the expression of tumor‐derived chemokines/cytokines that facilitated the recruitment of protumor myeloid populations. Depletion of MDSCs was accompanied by reduced TAM infiltration and phenocopied the antimetastatic effects of p38i. Reciprocally, p38i increased tumor infiltration by cytotoxic CD8 + T cells. Furthermore, the CD163 + /CD8 + expression ratio inversely correlated with metastasis‐free survival in breast cancer, suggesting that targeting p38 may improve clinical outcomes. Overall, our study highlights a previously unknown p38‐driven pathway as a therapeutic target in MBC. Abstract : What's new? Tumor‐induced mobilization of myeloid cell populations has been linked to metastatic progression and unfavorable outcome in metastatic breast cancer. The underlying mechanisms for these relationships remain unclear, however. This study demonstrates that the p38 kinase controls tumor‐driven expansion of the myeloid compartment. Genetic or pharmacologic inhibition of p38 reduces the accumulation of tumor‐associated macrophages and myeloid‐derived suppressor cells and impedes tumor angiogenesis and metastasis. Altogether, this study provides evidence for a novel mechanism by which p38 promotes metastasis, and indicates that targeting this pathway may have important implications for cancer immunotherapy.